Size selection in codends made of thin-twined Dyneema netting compared to standard codends: a case study with cod, plaice and flounder - Herrmann, Bent; Wienbeck, Harald; Stepputtis, Daniel; Ahm Krag, Ludvig; Feekings, Jordan P.; Moderhak, Waldemar (Fisheries Research, 2015)
In an experimental trawl fishery, diamond mesh codends made out of 2.5 mm flexible Dyneema twine were tested. The principle aim was to investigate the effect of the number of meshes in the codend circumference, the number of twines (single or double), and netting orientation (T0 or T90) on the size selection of cod (Gadus morhua), plaice (Pleuronectes platessa) and flounder (Platichthys flesus). In addition, the obtained size selectivity for the codends made of Dyneema netting were compared to results obtained for T90 codends made of standard 5 mm single twine PE netting, and to previous results for other PE codends used in the same fishery. It was observed that the selective performance of the Dyneema netting codends was very high compared to other T0 and T90 codends of the same mesh size and number of meshes in the codends circumference. This demonstrates the high selective potential of the thin and flexible Dyneema netting compared to nettings which are traditionally used in the construction of trawl codends. Furthermore, reducing the number of meshes in the codend circumference for the Dyneema codends significantly increased the size selection of cod but did not affect the size selection of plaice and flounder. This difference between the species is likely linked to their different morphologies. No differences in the size selection of the T0 and T90 designs made of Dyneema twine tested were observed for any of the three species. For cod, the effect of using single or double twine in the Dyneema codends was also tested, however, no significant differences were found.